1999
DOI: 10.1149/1.1391899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen on Semiconductivity of Passive Films and Corrosion Behavior of 310 Stainless Steel

Abstract: Hydrogen damage is a severe problem that refers to the degradation of mechanical properties of a metal caused by the presence of, or interaction with, hydrogen. The reduction of hydrogen ions is a source of atomic hydrogen. Hence, corrosion reactions, the application of cathodic protection and electroplating, etc., are major sources for introducing hydrogen into metals. During these hydrogen-generating processes, some of the reduced hydrogen may be absorbed on the metal surface and diffuse into the metals. [1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…Taking the half-height of the oxygen in Fig. 6 as an estimate of the film/substrate steel interface, 22) the passivated films formed on the non-coupled and coupled Alloy 600 with the magnetite require approximately 24 and 17 s of etching, respectively. This indicates that galvanic coupling between Alloy 600 and the magnetite formed the thinner and less protective passive film of Alloy 600.…”
Section: Corrosion Behavior Of Alloy 600 Coupled With the Magnetitementioning
confidence: 99%
“…Taking the half-height of the oxygen in Fig. 6 as an estimate of the film/substrate steel interface, 22) the passivated films formed on the non-coupled and coupled Alloy 600 with the magnetite require approximately 24 and 17 s of etching, respectively. This indicates that galvanic coupling between Alloy 600 and the magnetite formed the thinner and less protective passive film of Alloy 600.…”
Section: Corrosion Behavior Of Alloy 600 Coupled With the Magnetitementioning
confidence: 99%
“…Yang found that the susceptibility of 310 SS to pitting is strongly influenced by hydrogen present in the specimens. 52 The presence of hydrogen in 310 SS causes an inversion of a surface film conductivity type from p to n-type. 52 The susceptibility of 310 SS to pitting can be correlated to the electronic properties and chemical composition of the passive film.…”
Section: Effect Of Ph On S Incorporation-the Sims Data Inmentioning
confidence: 99%
“…52 The presence of hydrogen in 310 SS causes an inversion of a surface film conductivity type from p to n-type. 52 The susceptibility of 310 SS to pitting can be correlated to the electronic properties and chemical composition of the passive film. The high susceptibility of the charged specimens to pitting corresponds to the n-type conductivity of the passive film, while low susceptibility is connected to p-type conductivity and high chromium and nickel oxide content.…”
Section: Effect Of Ph On S Incorporation-the Sims Data Inmentioning
confidence: 99%
“…This is likely due to the change in the composition and thickness of the passive film. The structure of passive film resembles that of a semiconductor (21) (28) . The iron oxides which act as dopants to chromium oxide in the native passive film are selectively dissolved during the potentiostatic test, and consequently results in decreased conductivity.…”
Section: Interfacial Contact Resistance (Icr)mentioning
confidence: 99%